Impactos socioambientais que ameaçam os serviços ecossistêmicos de regulação e manutenção no Parque Regional Corno Alle Scale nos Apeninos Bolonheses, Itália - Maria do Socorro Ferreira da Silva; Elisa Magnani; Fernando Luiz Araújo Sobrinho (Terr@ Plural)
this paper aims to identify regulation and maintenance Ecosystem Services (ESs) and the socio-environmental impacts in the Corno alle Scale Regional Park in Lizzano de Belvedere, Italy. The following procedures were carried out: bibliographic and documentary survey; field research; interviews; and analysis of information. 11 Regulation and maintenance Services were identified in the park — maintenance of biological diversity, biological control, climate regulation, water regulation, purification and maintenance of water supply, etc. These SEs deserve attention, as they are fundamental for providing various benefits to society. However, there are several impacts that threaten natural resources and SEs in the park, such as the production of artificial snow and the installation of cable cars, which cause impacts on the soil, water resources, biodiversity, thus disrupting the ecological balance. In this sense, tackling climate change is among the main challenges in managing the protected area, and it is crucial to seek strategies as alternatives to promote sustainable tourism in the Bolognese Apennines